SVO Word Order Errors in English-Arabic Translation - Sado Al-Jarf, Reima (Meta, 2007)
AbstractAn error corpus of deviant SVO structure was collected from the translation projects of students majoring in translation. Syntactic, semantic, pragmatic and discoursal criteria were used to judge the deviations. Percentages of interlingual and intralingual errors, the syntactic contexts in which subjects were misplaced, the strategies used to impose SVO order, and areas of L1 inadequate competence will be reported. Implications for increasing students’ awareness of the pragmatic, discoursal and syntactic constraints in translating SVO structures will be provided.